Notes on the subfamily Salyavatinae (Hemiptera: Reduviidae) from Vietnam, with the description of a new genus - Truong, Xuan Lam; Zhao, Ping; Cai, Wan Zhi (Zootaxa, 2007)
The Vietnamese genera and species of the assassin bug subfamily Salyavatinae are revised. Five species in four genera are recognized, described or redescribed, illustrated, and keyed. One new monotypic genus, Rhachicephala gen. nov., is established, with R. dilatibia sp. nov as the type species.